The Effectiveness of Mediation in Inheritance Law Disputes is Linked to Perma No. 1 of 2016 at the Karawang Religious Court - Dini Nurfalah; Amaliya, Lia; Abas, Muhamad (Dinasti Research, 2024)
Mediation as an alternative dispute resolution mechanism outside of court has long been used in various business, environmental, labor, land, housing, and so on cases that are fast, effective and efficient. Mediation comes from the English